2018
DOI: 10.1007/s00405-018-4997-1
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stage and pack-years, but not p16 or HPV, are relevant for survival in hypopharyngeal and laryngeal squamous cell carcinomas

Abstract: PurposeRecently, p16 has been included in the TNM guideline for oropharyngeal carcinomas. The role of HPV and p16 in hypopharyngeal and laryngeal carcinomas has not yet been established sufficiently.MethodsHundred and thirty-four patients with hypopharyngeal and laryngeal carcinomas were included in this retrospective analysis. Only patients with known HPV status were eligible for the investigation. Survival probabilities were estimated for different risk factors.ResultsEighty-five patients presented with lary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 21 publications
1
24
0
2
Order By: Relevance
“…As expected, patients with early stage HNSCC tumors (stages I–II) have longer OS than patients with advanced stage tumors (stages III–IV). The same findings were recently published in hypopharyngeal and laryngeal squamous cell carcinomas, where early stage tumors (stages I–II) presented a better overall survival than advanced stage tumors (III–IVc) [35]. Moreover, we found that tumors with differentiated histological grade have better RFS and OS than undifferentiated tumors.…”
Section: Discussionsupporting
confidence: 91%
“…As expected, patients with early stage HNSCC tumors (stages I–II) have longer OS than patients with advanced stage tumors (stages III–IV). The same findings were recently published in hypopharyngeal and laryngeal squamous cell carcinomas, where early stage tumors (stages I–II) presented a better overall survival than advanced stage tumors (III–IVc) [35]. Moreover, we found that tumors with differentiated histological grade have better RFS and OS than undifferentiated tumors.…”
Section: Discussionsupporting
confidence: 91%
“…As an important prognostic factor in head and neck carcinoma, human papillomavirus (HPV) status seems to be prevalent in oropharyngeal carcinoma. Dahm showed that HPV infection did exist in HC patients; however, there was no evidence for a better survival for HPV-positive patients with HC [26] .…”
Section: Discussionmentioning
confidence: 97%
“…12 The literature suggests also that hypopharynx carcinomas are more frequently HPV (-) than HPV (+). [23][24][25] These findings may speak in favor of a similar molecular origin of Zenker's carcinoma, HPV (-) HNSCC, and hypopharynx carcinoma. However, a reliable comparison between Zenker's carcinoma and hypopharynx carcinoma is challenging because the available data about the molecular origin of hypopharynx carcinomas are also limited.…”
Section: Discussionmentioning
confidence: 88%
“…The literature suggests also that hypopharynx carcinomas are more frequently HPV (‐) than HPV (+) 23‐25 . These findings may speak in favor of a similar molecular origin of Zenker's carcinoma, HPV (‐) HNSCC, and hypopharynx carcinoma.…”
Section: Discussionmentioning
confidence: 93%